A Vida de S. Francisco de Salles (Livraria Figueirinhas- Editora, 1907)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Boletim Official do Governo da Provincia de Macau (IMPRENSA NACIONAL, 1907)
Stamp of St. Joseph Seminary
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage

Catechismus Romanus, Ex Decreto Concilii Tridentini (Sumptibus Et Typis Friderici Pustet, 1907)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Catecismo, Filosofico= Teologico de Religion (Subirana Herms, Editores Pontificos, 1907)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Elementa Grammaticae latinae ad usum tironum sinensium (Typis Pei-T'ang, 1907)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; languages

Compendio de Historia Eclesiastica General - Aguilar, Francisco de Asis (Libreria Catolica de D. Gregorio del Amo, 1907)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Compendio de Historia Eclesiastica General - Aguilar, Francisco de Asis (Libreria Catolica de D. Gregorio del Amo, 1907)
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 2.Damage

Annaes da propagação da fé - Associação da Propagação da Fé (Na Typ. de G. M. Martins, 1907)
Keywords: 2.Damage; Condition: Fair; Missões [Periódicos]; Religion

Annaes da propagação da fé - Associação da Propagação da Fé (Na Typ. de G. M. Martins, 1907)
Keywords: 2.Damage; Condition: Fair; Missões [Periódicos]; Religion

Annaes da propagação da fé - Associação da Propagação da Fé (Na Typ. de G. M. Martins, 1907)
Keywords: 2.Damage; Condition: Fair; Missões [Periódicos]; Religion

Annaes da propagação da fé - Associação da Propagação da Fé (Na Typ. de G. M. Martins, 1907)
Keywords: 2.Damage; Condition: Fair; Missões [Periódicos]; Religion

Annaes da propagação da fé - Associação da Propagação da Fé (Na Typ. de G. M. Martins, 1907)
Keywords: 2.Damage; Condition: Fair; Missões [Periódicos]; Religion

Compte Rendu du Congres Marial International, Tenu a Einsiedeln en Suisse - Battaglia, F. (Revue Mariale, 1907)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

O padre junto aos doentes e moribundos - Carlos das Neves (Livraria Catholica Portuense, 1907)
Keywords: Good

O Padre Junto aos Doentes e Moribundos - Carlos das Neves (Livraria Catholica Portuense, 1907)
Keywords: Good

Dictionarium sinicum & latinum ex radicum ordine dispositum - Couvreur, Séraphin (Ex Missione catholica S.J., 1907)
汉文拉丁文字典》
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Chinese language; Condition: Fair; Dictionaries; Hard Cover; languages

Tratado de physica elementar - Francisco Ribeiro Nobre (Livraria Chardron, 1907)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Teaching

Theses de Ecclesia Christi, Opus Posthumum - Franzelin, Ioannis Bapt. (Ex Typographia Polyglotta, 1907)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

The Catholic encyclopedia: an international work of reference on the constitution, doctrine, discipline, and history of the catholic church - Herbermann, Charles George (Robert Appleton Co., 1907)
Keywords: Catholic Church; Catholic Church Dictionaries; Condition: Fair; Dictionaries; Encyclopedias and dictionaries; Hard Cover; Theology; Theology Dictionaries; Église catholique Dictionnaires anglais

The Catholic encyclopedia: an international work of reference on the constitution, doctrine, discipline, and history of the catholic church - Herbermann, Charles George (Robert Appleton Co., 1907)
Keywords: Catholic Church; Catholic Church Dictionaries; Condition: Fair; Dictionaries; Encyclopedias and dictionaries; Hard Cover; Theology; Theology Dictionaries; Église catholique Dictionnaires anglais

Vida de S. Domingos - Lacordaire, R. P. Henri-Dominique (Typ. da Livraria Ferin, 1907)
Stamp of St. Joesph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Compendium Theologiae Moralis - Lehmkuhl, Augustino (Sumptibus Herder, 1907)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Compendium Theologiae Moralis - Lehmkuhl, Augustino (Sumptibus Herder, 1907)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

La Medecine Pastorale - Lehmkuhl, P. (P. Lethielleux, Libraire-Editeur, 1907)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage; 6.Yellowing 變黃

Les vaillantes du devoir : études féminines - Leon Rimbault (Ancienne Maison Charles Douniol, 1907)
Keywords: 2.Damage; Condition: Fair; Hard Cover

Catecismo Para os Parochos - Marinho, Manuel (1907)
Keywords: 1.Conservation 保護; 2.Damage

Rosario d'amor. Sonetos ... trasladados do provençal a vulgar [i.e. into Portuguese] por J.M. Greenfield de Mello - MONNÉ, Jean; MELLO, J. M. Greenfield de (1907)
Keywords: 2.Damage; Condition: Fair

Tentações de Sam Frei Gil - Oliveira, António Correia de (Ferreira & Oliveira, 1907)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Literatura portuguesa Séc. 19-20; Literature; Poesia portuguesa Séc. 19-20

Obras completas do Padre António Vieira. Sermões - Padre Goncalo Alves (Livraria Chardron, 1907)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Religion

Obras completas do Padre António Vieira. Sermões - Padre Goncalo Alves (Livraria Chardron, 1907)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Religion

Vers L'Action - Pechenard, P. L (Librairie Bloud & cie., 1907)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Portugal Diccionario Historico - Pereira, esteves, e Rodrigues, Guilherme (Joao Romano Torres, 1907)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Dictionaries; History

Novo methodo de leitura - San-Tok-Pun (Tip. Mercantil, 1907)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Literature; Macau

Les Litanies du Coeur de Jesus - Sauve, Charles (Vic et Amat, Libraires-Editeurs, 1907)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Institutiones cosmologiae - Schaaf, H. (Giachetti, 1907)
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Cosmologie; Cosmology; Hard Cover; Science Study and teaching; Travel; cosmology

Nos fins dernières; souvenir d'une retraite prêchée aux mères chrétiennes de la paroisse Saint-Martin du Cateau, les 7,8,9 Mars 1907 - Smet, Laurent de (Desclée de Brouwer, 1907)
Keywords: Condition: Fair; Religion

The Historians' History of the World - William, Henry Smith (Title-Page Designed and Gngraved, 1907)
Keywords: 1.Conservation 保護; 10.Cover Damage

The Historians' history of the world: a comprehensive narrative of the rise and development of nations as recorded by the great writers of all ages - Williams, Henry Smith; McNeill, Ronald (The Times, 1907)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Histoire universelle; History; World history